2011
DOI: 10.1124/jpet.111.183798
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neuronal Nitric-Oxide Synthase in Estrogen-Induced Relaxation in Rat Resistance Arteries

Abstract: Estrogen has antihypertensive and vasorelaxing properties, partly via activation of endothelial nitric-oxide synthase (eNOS). Recently, neuronal nitric-oxide synthase (nNOS) has been detected in vascular cells, although the significance of this is unclear. Estrogen was found to stimulate nNOS in certain cultured cells. We hypothesized that estrogen regulates vascular tone partly via endothelium-derived nNOS. Human umbilical vein endothelial cells were used to test whether acute (5 min) stimulation with 17␤-est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 37 publications
4
28
1
4
Order By: Relevance
“…Several groups have used L-NPA at micromolar concentrations in different systems to demonstrate selective nNOS inhibition (3,11). A recently published study from our group has shown that similar concentrations of L-NPA can indeed inhibit nNOS in the vasculature without affecting eNOS-dependent vascular functions (33). Ongoing work in our laboratory also suggests similar effects of 2 M L-NPA compared with small interfering RNA-mediated downregulation of nNOS protein in HUVECs (data not shown).…”
Section: E 2 Attenuates High Glucose-induced Nitrotyrosine and Peroxysupporting
confidence: 65%
See 1 more Smart Citation
“…Several groups have used L-NPA at micromolar concentrations in different systems to demonstrate selective nNOS inhibition (3,11). A recently published study from our group has shown that similar concentrations of L-NPA can indeed inhibit nNOS in the vasculature without affecting eNOS-dependent vascular functions (33). Ongoing work in our laboratory also suggests similar effects of 2 M L-NPA compared with small interfering RNA-mediated downregulation of nNOS protein in HUVECs (data not shown).…”
Section: E 2 Attenuates High Glucose-induced Nitrotyrosine and Peroxysupporting
confidence: 65%
“…Classically, eNOS has been considered the main source of NO in the vasculature, although there is increasing evidence that nNOS in the endothelium plays an important function (4,9,10,17). Recently, we have demonstrated the presence of endothelial nNOS in rat mesenteric arteries where this enzyme contributes to a vasorelaxant role (33). The beneficial vascular effects of estrogen are believed to be largely mediated through increased endothelial NO synthesis (1,2,22).…”
mentioning
confidence: 94%
“…Physiologically, the two forms of nitrogen oxide synthase can be distinguished as the constitutive form (cNOS) and the inductive form (iNOS) [37]. The constitutive form, present in nervous tissue (nNOS) and in endothelial cells (eNOS), comprises up to 95% of the total synthase activity [25]. Interestingly, the nNOS isoform was discovered only a few years ago in endothelial cells.…”
Section: Immunohistochemical Markers Of Endothelial Cellsmentioning
confidence: 99%
“…In addition, increased oestrogen may cause peripheral artery vasodilation and reduce the TPR, which may cause lower AI (Hayashi et al 1995). Oestrogen has been demonstrated to increase production of both nitric oxide (NO) and prostacyclin by upregulating endothelial nitric oxide synthase (eNOS) activity and prostacyclin synthase via a receptormediated system in which it promotes vasodilation (Hayashi et al 1995;Massion & Balligand 2003;Lekontseva et al 2011). Further study has reported that the physiological changes observed during the luteal phase of menstrual cycle does cause a marked decrease in TPR and a significant decrease in mean arterial pressure in the mid luteal phase corresponding to oestrogen level (Hassan et al 1990).…”
Section: The Effects Of Menstrual Cycle On Aimentioning
confidence: 99%